Thoughts About the Сrisis - A. A. Orlov (Vestnik MGIMO-Universiteta, 2012)
The author analyses the causes and possible consequences of the actual financial and economic crisis, expresses the opinion that it can take a form of chronic disease and have significant duration of time. In opinion of the author, it's necessary now to take adequate measures to elaborate principles of new world economic model.